Shakespeare revisité, entre fidélité et parodie : de La Nuit des Rois à Shake de Dan Jemmett - Isabelle Schwartz-Gastine (Revue LISA)
William Shakespeare himself was a master of re-writing older material as he abundantly used this technique, which was totally justified at the Renaissance, to compose his poems or plays, from various sources whether literary (prose or verse), historical, or any other—and sometimes most unusual—background.The play I am considering in this paper is a very recent re-writing in English by Dan Jemmett (Peter Brook’s son-in-law), but performed in Marie-Paul Remo’s French translation at the Vidy Theatre in Lausanne during the 2001 season. It is called Shake, with a modest sub-title « around Twelfth Night », but which is indeed at the heart of the topic.Through the exploration of three themes: symmetry (of situations, of twin binarities), love’s misunderstanding, and music, I will argue that this comedy, whose title is a mix between the name of the Bard and the etymological meaning of the verb “to shake” as far as traditions are concerned, is faithful to the spirit (rather than the letter) of the Shakespearean original in a very healthy comic vein.It is not worth wondering if the spectators fully understood the meaning of this comedy in which the four actors change roles all the time: their frequent bursts of laughter clearly showed that they enjoyed the spirit of the comedy, whether they knew Twelfth Night or not.